D-Dimer and Carcinoembryonic Antigen Levels: Useful Indicators for Predicting the Tumor Stage and Postoperative Survival - Kemal Tekeşin; Savaş Bayrak; Varol Esatoğlu; Ebru Özdemir; Leyla Özel; Veli Melih Kara (Gastroenterology Research and Practice)
The purpose of this prospective study is to determine the preoperative plasma D-dimer and serum Carcinoembryonic Antigen (CEA) levels of patients scheduled for curative surgical resection for colorectal cancer and to evaluate the significance of these levels on the prognosis and postoperative survival rate. One hundred sixty-five patients with colorectal cancer, who were scheduled to have elective resection between January 2008 and January 2011, were included in the study. A significant increase was observed in the D-dimer levels, particularly in poorly differentiated tumors. The distance covered by the tumor inside the walls of the colon and rectum (T-stage) was significant for both D-dimer and CEA levels. As the T-stage increased, there was also a significant increase in the D-dimer and CEA levels. A high significance and correlation level was detected between the TNM staging and both D-dimer and CEA. A significant relationship was found between the advanced tumor stage and short postoperative survival rate of patients with colorectal cancer. Therefore, the analysis of preoperative D-dimer and CEA levels can be useful in predicting the stage and differentiation of the tumor and the postoperative survival rate.